Three essays in applied microeconomics with policy implications - Adam, Aisha Ibrahim (Kansas State University, 2024)
In this dissertation, I investigate three distinct topics in applied microeconomics that focus on human behavior and public policy. In my first essay, I examine how colonial medical campaigns organized in Cameroon in West Africa impact COVID-19 vaccine hesitancy in neighboring Nigeria. Specifically, I study how distance from historical medical campaign sites in Cameroon affects the likelihood that Nigerians today would willingly accept a free, safe COVID-19 vaccine. I find that a 1000-kilometer increase in distance from colonial medical campaign sites is correlated with a 15.8 percentage point increase in the likelihood that Nigerians will accept a free safe vaccine. Examining potential transmission mechanisms reveals that my result can partially be explained by Nigerians’ mistrust in their government, traditional, and religious authorities and institutions. This finding establishes persistent long-run spillover effects of colonial medical campaigns into neighboring countries. My second essay examines how Project Hope, a maternal healthcare intervention in Cross Rivers State, Nigeria impacts the likelihood of ever attending antenatal care, attending antenatal care before 12 weeks’ gestation and receiving blood pressure checks during pregnancy. Using data from the Nigerian Demographic and Health survey, I conduct a difference-in-differences analysis to estimate the before and after effects of Project Hope. I find that while Project Hope increases the likelihood of early antenatal care attendance before 12 weeks’ gestation by 19.2 percentage points, it does not significantly impact the likelihood of receiving a blood pressure check or the likelihood of ever attending antenatal care. My findings establish that maternal healthcare interventions reduce barriers to accessing critical healthcare services during pregnancy and may improve outcomes for mothers and their babies. My third essay isolates the effects of English language ability on female labor force participation in the United States using different samples of childhood female immigrants including those who are now married women and mothers. I use an instrumental variables model that interacts coming from a non-English speaking country with arriving in the US at a young age to identify the effect of English language proficiency on immigrants’ labor force participation. Speaking English well leads to a 21-percentage point increase in the likelihood of future labor force participation for female childhood immigrants to the US, all else equal. My results hold steady for different categories of female immigrants and are largest for those women with young children at home. I also show that English language ability may be acting through increasing educational attainment to affect labor force participation for female immigrants.
Keywords: Microeconomics; Colonialism; Maternal health; Immigration; Difference-in-differences; Instrumental variables